A preliminary study on radon concentrations and health risk assessment of drinking water samples in kilis province, Turkey - Canbazoglu, Cumhur; Gundogan, Ayse; Bal, Sultan Sahin; Dogru, Mahmut (Parlar Scientific Publications, 2020)
Determination of radon concentration in drinking water is very important to assessment whether it poses a health risk in terms of public health or not. For this purpose, radon (2 2 2Rn) concentration of forty nine drinking water samples collected from Kilis province were determined by using CR-39 passive nuclear track detectors with closed-can technique in this study. The radon concentrations for drinking water samples were found between 0.69 and 6.93 Bq L-1 with average of 1.86 Bq L - 1 . All obtained values for radon concentrations were below 11.1 Bq L-1 that recommended as maximum contaminant level (MCL) by the United States Environmental Protection Agency (USEPA). In addition, effective dose and population weighted fatal cancer risk due to 2 2 2 R n in drinking waters were estimated. Average effective dose values were calculated to be 4.75 ?Sv y-1, 4.69 ?Sv y- 1, 0.57 ?Sv y- 1 and 0.56 ?Sv y- 1 for ingestion, inhalation, stomach and lungs, respectively. All obtained effective dose values were well below the reference level that suggested as 0.1 mSv y-1 by Word Health Organization (WHO). Population weighted fatal cancer risk varied from 2.62E-06 to 2.54E-04 and average value was found to be 3.07E-05 for Kilis province. In addition, per caput risk was estimated 1.99E-08 due to radon in drinking water samples. Investigated water samples for Kilis province were well below the permissible limits and have no risk to public health. © 2020 Parlar Scientific Publications. All rights reserved.
Keywords: Annual effective dose; Cancer risk; Closed-can technique; Drinking water; Kilis; Nuclear track detectors; Radon